Cytotoxic effects and apoptosis induction of betulinic acid on WEHI-3B (murine myelomonocytic leukemic) cells - 'Ali Zainal 'Abidin bin Nordin
Betulinic acid (3P-hydroxy-Iup-20(29)-ene-28-oic acid) is a pentacyclic triterpene. The compound can be chemically synthesized from betulin. Both natural compound can be isolated from the bark of Melalueca cajuputi of a local plant. Betulinic acid (BA) was reported to possess several biological activities such as anti-inflammatory, anti-viral, anti-tumor and anti-plasmodial. Selective cytotoxic activity against neuroectodermal origin cancer and leukemic cancer cell lines were also rep rted, Furthermore, the compound has been shown to cause apoptosis in a number of cancer cell lines but en a little to no toxicity against normal cells. The objective of the study was to evaluate cytotoxic effects and apoptosis cell death of BA on BALB/C murine myelomonocytic leukemia (WEHI-3B). The cell line was selected because it can be used to induce leukemia by injection into BALB/c mice which later can be used to evaluate in vivo anti-leukemic activity. The cytotoxic and anti-proliferative studies ofBA in WEHI-3B were carried out by using 3-[ 4,5-dimethylthizol-2-yIJ-2,5-diphenyltetrazolium bromide (MTT) assay. The cytotoxic dose fifty percent (CDso) value was obtained from the dose response curve of percentage viability against concentration of BA. The anti proliferative activity was determined by comparing the proliferation of different cytotoxic doses and also comparing with untreated (control) for 24, 48 and 72 hours treatment. The effect of compound on cell cycle phases of WEHI-3B cells were observed by comparing cell cycles profiles of the treated and untreated WEHI-3B cells analyzed using flow cytometer analysis. Apoptotic and necrotic cells were scored by observing the cells under the inverted flourescence microscope post staining with Acridine Orange and Propidium Iodide (AOPI) dyes. Annexin V IPI double staining was used to recognize stages and characteristics of apoptosis. The mechanism of apoptosis was studied from the involvement of caspases in caspase activity assay. BA displayed active cytotoxic activity against BALB/c murine myelomonocytic leukemia (WEHI-3B), human myeloid leukemia (HL-60) and human breast cancer cell (MCF-7) but not on human normal colon cells (CCD-18Co), suggesting its action is specific for tumor cells. MTT assay result showed that the CDsovalue ofBA was 4.471lg/mL and considered to fall within the range of toxicity effect by the commercial drug, Vincristine sulphate (VCR). BA was able to show the same inhibitory effect as VCR on the growth and proliferation of WEHI-3B proved by the optical density of BA treatment CD dose 25, 50 and 75 were lower than the optical density of control. BA was found to arrest WEHI-3B at 00/01 phase in a time-dependent manner with significant result compared to control at 6 hours point (p=0.0001). Vincristine was found to arrest 02/M phase after 3 and 6 hour followed by 00/01 phase arrest at 12 and 24 hour of treatment with significant cell population percentage reduction compared to control at 12 (p=0.0024) and 24 hours (p<0.0001). Characteristic and stages of apoptosis in cells with BA treatment were detected under AOPI and Annexin V!PI double staining. Membrane blebbing, cell shrinkage and nuclear chromatin condensation were observed. Apoptotic effects ofBA were very significant (p<0.0001) when compared to control with throughout the 24,48 and 72 hours. Similarly, apoptotic percentage of BA treatment also showed very significant result (p<0.0001) when compared to VCR treatment. The primary mode of cell death in BA treatment was apoptosis even though there were necrosis detected. Apoptotic cell death percentage was higher than necrotic cell death when treated with BA for 24,48 and 72 hours. BA treated cells exhibited early apoptosis showing gradual increase pattern in time dependent manner. Caspase-8, -9 and -3 activity is also activated in a time-dependent manner compared to control. BA induced apoptotic cell death in WEHI-3B showing good potential as an anti-leukemic compound which later can be used in vivo model studies.